2011
DOI: 10.1080/15205436.2010.496136
|View full text |Cite
|
Sign up to set email alerts
|

The Conflict over Origins: A Discourse Analysis of the Creationism Controversy in American Newspapers

Abstract: The debate about human origins between creationists and biologists is hardly a new one. In its latest cycle, the dispute concerns the status of Intelligent Design and the teaching of evolutionary theory in public schools. The controversy is primarily political, motivated by deeply held feelings about identity. A discourse analysis using network modeling was applied to newspaper coverage of the controversy from September to December 2005, around the time of the Dover trial (Kitzmiller v. Dover Area School Distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Habertürk 1 Çiler, 2006) ya da daha saptayıcı bir tanıma muhafazakâr ve seküler/modern ayrışmasının yansıması olan bir tür kültür savaşı (Shortell, 2011) söz konusu edilebilir. Gazeteler, laiklik etrafındaki tartışmalarda kendi ideolojileri doğrultusunda kavramsal anlayışlar üretmektedirler ve laikliğin ya da seküler anlayışın medyadaki yeniden üretim süreçleri, laikliği ötekileşmenin öznesi veya nesnesi haline de getirebilmektedir (Öztaş, 2016).…”
Section: Gazete Funclassified
See 1 more Smart Citation
“…Habertürk 1 Çiler, 2006) ya da daha saptayıcı bir tanıma muhafazakâr ve seküler/modern ayrışmasının yansıması olan bir tür kültür savaşı (Shortell, 2011) söz konusu edilebilir. Gazeteler, laiklik etrafındaki tartışmalarda kendi ideolojileri doğrultusunda kavramsal anlayışlar üretmektedirler ve laikliğin ya da seküler anlayışın medyadaki yeniden üretim süreçleri, laikliği ötekileşmenin öznesi veya nesnesi haline de getirebilmektedir (Öztaş, 2016).…”
Section: Gazete Funclassified
“…Tarafsızlığı ve akla ya da bilime dayanmayı indirgemeci bir bakışla sadece iktidara ilişkin olumsuz ya da eleştirel bir duruş ile ilişkilendirmek haberleştirme sürecinde etkili olan diğer unsurların göz ardı edilmesine yol açmaktadır. Çünkü esasen toplumsal aktörler başkalarının dünya görüşlerini duymak ve onları ikna etmek için bir tür rekabet içerisindedirler(Shortell, 2011). Çok sayıda araştırmanın yanı sıra bu çalışmanın bulguları da siyasi duruşun iktidar yanlısı ya da karşıtı olmanın ötesinde etkileri olduğunu ve bu etkilere bağlı olarak haberleştirme süreçlerinin ideolojik kamplaşmaların yansımalarına dönüştüğünü göstermektedir.…”
unclassified
“…A number of recent studies have focused attention on the last step. In the last five years alone these include network text analyses of abstracts of academic journal articles (Beam, et al, 2014), medical school mission statements (Grbic, Hafferty, & Hafferty, 2013), presidential inaugural addresses (Light, 2014), violent extremist propaganda (Morris, 2014), screenplays and novellas (Hunter & Singh 2015;Hunter & Smith, 2014), energy policy speeches (Shim, Park, & Wilding, 2015), as well as newspaper articles about the global financial crisis (Nerghes, Lee, Groenewegen, & Hellsten, 2015), mad cow disease (Lim, Berry, & Lee, 2015), the creationism debate in the US (Shortell, 2011) and two major cities in Afghanistan (Martin, Pfeffer, & Carley, 2013). In these studies, measures of concept position within the text networks include degree centrality (Shortell, 2011;Grbic, Hafferty, & Hafferty, 2013;Martin, Pfeffer & Carley, 2013;Morris, 2014;) , betweenness centrality (Light, 2014;Shim, Park, & Wilding, 2015;Nerges, Groenewegen, & Hellsten, 2015), and network constraint (Hunter & Singh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown media coverage to be pro-ET (Allgaier, 2010; McCune, 2003; Martin et al, 2006; Shortell, 2011), others suggest that journalistic norms of neutrality serve to legitimate anti-evolutionists (Rosenhouse and Branch, 2006; Taylor and Condit, 1988) or that deficiencies in the presentation of evolution provide opportunities for creationist arguments (Dingwall and Aldridge, 2006). This study builds on existing scholarship by focusing on letters to the editor, which are more likely to accommodate marginalized perspectives such as anti-evolutionism.…”
Section: Introductionmentioning
confidence: 99%